Analisis Strategi Peningkatan Pendapatan Asli Daerah (PAD) Kabupaten Lima Puluh Kota - Nurdin, Salsabila; Devy, Tartila (ARZUSIN, 2026)
The issue of regional fiscal independence has become an important concern in local government financial management, particularly in regions that still depend on transfer funds from the central government. This study aims to analyze strategies for increasing Regional Original Revenue (PAD) in Lima Puluh Kota Regency and to identify the supporting and inhibiting factors in their implementation. This study used a qualitative approach with a case study design. The research informants were selected through purposive sampling, including representatives of the BPKPD of Lima Puluh Kota Regency and Bapelitbang who were involved in the management and planning of regional revenue. Data were collected through observation, semi-structured interviews, and documentation, and were then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that strategies for increasing PAD were implemented through enforcing taxpayer compliance, improving supervision, optimizing revenue sources, digitalizing payments, and exploring new revenue potential. However, the implementation of these strategies still faced obstacles, including low taxpayer compliance, limited access of the local government to potential revenue objects, and suboptimal management of regional assets. The conclusion of this study emphasizes the importance of planned, transparent, and locally based PAD governance to strengthen regional fiscal independence. The implications of this study provide practical contributions for local governments in formulating more adaptive, accountable, and regionally oriented strategies for increasing PAD.